2022
DOI: 10.1158/2159-8290.cd-21-1491
|View full text |Cite
|
Sign up to set email alerts
|

BAF Complex Maintains Glioma Stem Cells in Pediatric H3K27M Glioma

Abstract: Diffuse midline gliomas are uniformly fatal pediatric central nervous system cancers, refractory to standard of care therapeutic modalities. The primary genetic drivers are a set of recurrent amino acid substitutions in genes encoding histone H3 (H3K27M), which are currently undruggable. These H3K27M oncohistones perturb normal chromatin architecture, resulting in an aberrant epigenetic landscape. To interrogate for epigenetic dependencies, we performed a CRISPR screen and show that patient-derived H3K27M-glio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…BRD9 is a component of the non-canonical BAF chromatin remodelling complex (ncBAF) 35 and has recently been shown to constitute a barrier in reprogramming of somatic cells to induced pluripotent stem cells 36 . The catalytic component SMARCA4 of the BAF complex regulates stem cell properties in pediatric gliomas and provides a possible therapeutic angle in glioblastoma treatment 37 . Collectively these data provided evidence to focus our investigation on the molecular role of the BAF complex and BRD9 in particular, in PDAC CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…BRD9 is a component of the non-canonical BAF chromatin remodelling complex (ncBAF) 35 and has recently been shown to constitute a barrier in reprogramming of somatic cells to induced pluripotent stem cells 36 . The catalytic component SMARCA4 of the BAF complex regulates stem cell properties in pediatric gliomas and provides a possible therapeutic angle in glioblastoma treatment 37 . Collectively these data provided evidence to focus our investigation on the molecular role of the BAF complex and BRD9 in particular, in PDAC CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…These include oncogenic fusion of the BAF subunit SS18 with an SSX protein in synovial sarcoma and interaction of BAF with EWS-FLI1 in Ewing sarcoma causing aberrant BAF complex targeting 74,75 , subunit overexpression 76 , and heterozygous missense mutations within the Brg1 subunit gene in diverse cancers, several of which were characterized as gain-offunction for remodeling activity 77 . Furthermore, genetic dependency on Brg1 observed in several cancers has led to the emergence of pharmacological inhibition of the BRG1 ATPase activity as a novel therapeutic strategy [78][79][80] . Our study explains how BAF can synergize with cell-typespecific chromatin regulators and TFs, shedding light into how BAF functions may be hijacked in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…H3C1 is a member of histone family ( 30 ). Missense mutations in histone related genes promote tumor progression, a process known as oncohistones, which is a major challenge for tumor treatment ( 31 , 32 ). Yi.H et al revealed for the first time that high expression of histone deacetylase 7 (HDAC7) was closely associated with poor in EC, suggesting that HDAC7 is a potential cancer-promoting agent ( 33 ).…”
Section: Discussionmentioning
confidence: 99%